MONITORING PERDAGANGAN INVERTEBRATA LAUT SEBAGAI SPESIMEN AKUARIUM DI SURABAYA - Indrawati, Putri; Tanziyah, Lia Li Anatus; Widiyawati, Eka (Sains & Matematika, 2016)
Saat ini perdagangan hewan invertebrata semakin marak, namun belum ada data tentang jenis-jenis hewan tersebut serta bagaimana status konservasinya. Penelitian ini bertujuan mengidentifikasi jenis-jenis invertebrata laut sebagai spesimen akuarium yang diperdagangkan di Pasar Ikan Gunung Sari, Surabaya; mendeskripsikan status perlindungan invertebrata laut; mendeskripsikan cara perolehan (asal) hewan invertebrata laut yang diperdagangkan; serta mendeskripsikan keterlibatan masyarakat dalam perdagangan invertebrata laut sebagai spesimen akuarium Pasar Ikan Gunung Sari, Surabaya berdasarkan alasan pembelian, frekuensi pembelian, dan pengetahuan masyarakat tentang hewan yang dibeli. Penelitian dilakukan dengan menggunakan metode observasi hewan yang diperdagangkan dan wawancara terhadap pedagang dan pembeli hewan invertebrata. Terdapat 29 spesies invertebrata laut yang diperdagangkan sebagai spesimen akuarium di Pasar Ikan Gunung Sari Surabaya, tiga di antaranya termasuk hewan dilindungi. Selain itu, terdapat empat spesies yang termasuk kategore Least Concern menurut IUCN adan 15 spesies termasuk apendiks II CITES.Nowadays, the trading of invertebrate animals are increasing, however there is no data about the species of these animals and the status of their conservation. The purposes of this research were to identify the sea invertebrates as specimen of aquarium traded in Pasar Ikan Gunung Sari, Surabaya; describe the conservation status of sea invertebrates; describe the origin of those traded animals; and describe the role of the society in the trading of aquarium specimen in Pasar Ikan Gunung Sari, Surabaya based on the reason of the purchase, the frequency of purchase, and the knowledge of peoples about animals that they bought. This research conducted using observation methods, namely by observing of the animals that are traded and conducted interviews to the traders and buyers of invertebrates. In Pasar Ikan Gunung Sari, there were four shops that sell sea invertebrates. There were 29 species of sea an invertebrate are traded and was found three species of them were protected based on Government Regulations. In addition, there were four species which were classified as Least Concern according to IUCN and 15 species which were classified as Appendix II according to CITES. The sea invertebrates are obtained from suppliers routinely from the sea in Banyuwangi, Situbondo, Bali and Papua. The buyers were sea animal?s lovers who collected sea invertebrates to decorate their aquariums, but they do not know the conservation status protected of the animals.